Long-Term Presence of the Island Mass Effect at Rangiroa Atoll, French Polynesia - Vollbrecht, Carleigh; Moehlenkamp, Paula; Gove, Jamison M.; Neuheimer, Anna B.; McManus, Margaret A. (Frontiers in Marine Science, 2021)
Enhancement of phytoplankton biomass near island and atoll reef ecosystems – termed the Island Mass Effect (IME) – is an ecologically important phenomenon driving marine ecosystem trophic-structure and fisheries in the midst of oligotrophic tropical oceans. This study investigated the occurrence of IME at Rangiroa Atoll in the French Polynesian Tuamotu archipelago, and the physical mechanisms driving IME, through the analysis of satellite and in situ data. Comparison of chlorophyll-a concentration near Rangiroa Atoll with chlorophyll-a concentration in open ocean water 50 km offshore, over a 16-year period, showed phytoplankton enhancement as high as 130 % nearshore, over 75.7 % of the study period. Our statistical model examining physical drivers showed the magnitude of IME to be significantly enhanced by higher sea surface temperature (SST) and lower photosynthetically active radiation (PAR). Further, in situ measurements of water flowing through Tiputa Channel revealed outflowing lagoon water to be warmer, lower in salinity, and higher in particulate load compared to ocean water. We suggest that water inside Rangiroaʻs lagoon is enriched in nutrients and organic material by biological processes and advected as a result of tidal and wave forcing to coastal ocean waters, where it fuels primary production. We suggest that a combination of oceanographic and biological mechanisms are at play driving frequency and magnitude of IME at Rangiroa Atoll. Understanding the underlying processes driving IME at Rangiroa is essential for understanding future changes caused by a warming climate and changing environmental conditions for the marine ecosystem.